Analisis Kinerja Inspektorat Daerah Kota Serang Dalam Melakukan Pengawasan Internal Pada Tahun 2023 - Setya, Saefa Faris; Darmawan, Ivan (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to determine and analyze the performance of the Serang City Regional Inspectorate in 2023 in carrying out its duties and functions to supervise the performance of civil servants. The method used in this research is a literature study method in which data is collected through sources such as books- books, journal articles, and supervisory report documents as well as other documents sourced from the internet. The results obtained show that the Serang City Regional Inspectorate has carried out its internal supervision duties quite well, but there are still several obstacles that need to be corrected. Some of these obstacles include a lack of competent human resources, limited budget, and continued resistance from several supervised parties. To overcome these obstacles, it is necessary to increase the capacity and competence of human resources, increase the budget, and increase cooperation with related parties. It is hoped that this research can contribute to improving the performance of the Serang City Regional Inspectorate in carrying out more effective and efficient internal supervision in the future.